Interpersonal Skill Requirements for Fresh Computer Programmers: Expectation of Brunei-Based Organisations - A. Rahman, Mohd. Noah; Rahim, Md. Mahbubur; H. Seyal, Afzaal; Hj. Awg Mohamed, Hj. Awg Yussof (Malaysian Journal of Computer Science, 1999)
Computing is a rapidly changing technology. To compete successfully in this highly dynamic area, programmers tend to place more emphasis on technical know-how, and may ignore the importance of developing interpersonal skills. This study involves a survey of nearly 40 Brunei based organisations and reports the immense requirements of interpersonal skills expected from fresh programmers. This useful finding is discussed in detail, and some suggestions are offered to both academics and practitioners.